2021
DOI: 10.1177/21582440211066917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Personality Traits and Demographic Factors on Risk Attitude

Abstract: Numerous studies recently have explored how personality traits, risk attitudes and gender interact, with ambiguous results for different environmental and cultural contexts. To contribute to the existing literature, this study tests the relationship of individual risk attitudes with personality traits, and other variables, in the Czech Republic using the validated Czech version of the Big Five Inventory instrument. The results of an ordinal logistic regression show that risk aversion relates positively to neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…The second part of the study discovered that demographic factors such as age, race, employment status, educational level, and ELV ownership significantly impacted attitude. These findings support previous research that found age, employment status, educational level, and ELV ownership to be factors capable of predicting individual attitudes toward environmental policies (Schmidt et al, 2018;Guan et al, 2019;Zhao et al, 2019;Rahimi, et al, 2020;Pavlíček et al, 2021;Pratama and Firmansyah, 2021). Individuals of a mature age think more maturely than young people.…”
Section: Discussionsupporting
confidence: 89%
“…The second part of the study discovered that demographic factors such as age, race, employment status, educational level, and ELV ownership significantly impacted attitude. These findings support previous research that found age, employment status, educational level, and ELV ownership to be factors capable of predicting individual attitudes toward environmental policies (Schmidt et al, 2018;Guan et al, 2019;Zhao et al, 2019;Rahimi, et al, 2020;Pavlíček et al, 2021;Pratama and Firmansyah, 2021). Individuals of a mature age think more maturely than young people.…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with the above study. Also, the study found an influence of gender on risk aversion which indicated https://www.indjst.org/ men as less risk averse than women (10) . The parallel study showed the negative influence of conscientiousness, agreeableness and openness to experience on the risk which implies the person who possesses more of these traits tends to lower risk tolerance and the absence of influence was found between extraversion, neuroticism and risk.…”
Section: Literature Reviewmentioning
confidence: 89%
“…There has been a growing investigation of the relationship between risk preferences and personality traits across the Big-Five model (Lönnqvist et al, 2015;Baffour et al, 2019;Pavlíček et al, 2021). The findings revealed that people with a dominant extraversion (self-confidence, active and excitement seeking, positive emotions and intense personal interactions) and openness to experience (impulsive, willing to undergo new experiences and try new things, liberal in their values and flexible to norms) are more risk-tolerant.…”
Section: Risk Preferencesmentioning
confidence: 99%